"I was told it would help with my Psychology": Do post-16 Core Maths qualifications in England support other subjects?. Issue 1 (2nd January 2022) - Mathieson, Rachel; Homer, Matt
ABSTRACT: Continuing to study mathematics throughout schooling is considered important in most developed countries, where mathematics is incorporated within the curriculum until school-leaving age. By comparison, in England, relatively few post-16 (upper secondary) students study mathematics once it becomes optional. Core Maths qualifications, introduced in England in 2014, are intended to help increase post-16 mathematics participation. This paper uses data from a three-year, mixed-methods, longitudinal study to investigate a perceived benefit of the qualifications: the support Core Maths might give to other curriculum subjects in post-16 students' programmes. Amongst teachers and students, we find a widespread conviction that studying Core Maths benefits students' other subjects contemporaneously, whilst in national data from Core Maths students we find no evidence yet of enhanced examination attainment in other qualifications. We suggest that Core Maths impacts positively on students in ways which could be more usefully, and accurately, emphasised in promoting the course.